Medidas de aneurisma da aorta abdominal: modelos 3D impressos e virtuais - Gomes, Giovanna Ricarte Granja (2019)
Introduction: Two different methods can be used for elective treatment of abdominal aortic aneurysm: standard open surgery or endovascular repair. The first step of preoperative planning for both techniques is abdominal aortic angiotomography, to identify the type, location, size, magnitude of the aneurysm and involvement of the aortic branches. For endovascular treatment a second step is performed with a digital image processing software to obtain a two-dimensional (2D) or three-dimensional (3D) measurement of the parts of the disease and determine appropriate stent type according to the patient. This method is operator dependent therefore needs adequate training beforehand. A part of the aorta is printed by fast prototyping, a type of additive production technology where the 3D model uses the measurements acquired from abdominal angiotomography. For reconstruction, the instrument used for linear and angular measurements between reference points in medical images obtained through a DICOM (Digital Imaging and Comunications in Medicine) Viewer in PACS systems (Picture archiving and communication system) generates high accuracy measurements. The printing process is considered low cost, but the quality of the print is directly proportional to the model's production time. To date, few literature reports on the experience of using biomodels as preoperative planning in abdominal aortic aneurysm repair surgery have been published. Developing a device with accurate measurement techniques offers better anatomical visualization of each case, which may decrease radiation doses, time and surgical costs. Objective: To validate the implementation of 3D printed biomodels for metric and volumetric measurement of parts of the abdominal aortic aneurysm. In this context, we intend to compare the measurements obtained through computed tomography of the 3D biomodels with those performed in the Horos DICOM Viewer® software of patients submitted to endovascular correction of abdominal aortic aneurysms through VRMEsh® and NetFabb® software. Methods: The biomodels were produced by printing images from the DICOM archives of abdominal angiotomographies of patients submitted to endovascular surgery at the University Hospital of Santa Maria, in the period of 2016 to 2017. Conclusions: In metric and volumetric measurements, the tomography of the 3D printed biomodels is compatible with the three-dimensional images of the patient's angiotomography but cannot be used as a preoperative planning technique for abdominal aortic aneurysmectomy due to the need for mural thrombus measurement.